Different responses of luminal and glandular epithelium during mouse embryo implantation - Cui, Wenjing; Guan, Xiangrui; Liu, Peisen; Xu, Qi-Xin; Xie, Juan; Jiao, Yaqi; Jin, Lin; Wang, Peng-Chao; Yang, Zhenshan (Frontiers in Veterinary Science, 2025)
IntroductionEmbryo implantation, a crucial process for establishing and maintaining a successful pregnancy, involves the attachment and invasion of the embryo into the endometrium. The glandular epithelium (GE) within endometrial glands secretes multiple factors to support embryonic development, while the luminal epithelium (LE) covering the endometrial surface directly interacts with the embryo and regulates its invasion. This study uses RNA sequencing to examine the different responses of luminal epithelium (LE) and glandular epithelium (GE) during mouse embryo implantation.MethodsWe performed the RNA-seq using the mouse model of delayed and activated implantation to investigate the distinct regulatory mechanisms of LE and GE at 0 h, 3 h, and 6 h after initiating embryo implantation.ResultsThrough RNA sequencing and functional enrichment analysis of LE and GE tissues collected at different time points during activation, we revealed significant functional divergence between these two epithelial compartments across implantation stages. LE might predominantly regulate embryo attachment and initial invasion via activation of JAK-STAT, MAPK, and PI3K-Akt signaling pathways. In contrast, GE may exhibit specialized functions supporting embryonic development and maintaining the uterine microenvironment by modulating retinol metabolism, sphingolipid metabolism, and the Notch signaling pathway. Time-series analysis by Mfuzz further uncovered dynamic response patterns in both epithelial layers following progesterone administration. JAK-STAT and MAPK signaling pathways were significantly up-regulated in the LE after 3 h of treatment with estradiol-17β in mice. Retinol metabolism and glutathione metabolism signaling pathway were up-regulated in the GE after being treated with estradiol-17β in mice.ConclusionsRNA-seq results showed that LE and GE have different responses during mouse embryo implantation. These findings provide novel insights into the molecular mechanisms underlying embryo-endometrial crosstalk, offering valuable implications for developing therapeutic strategies for implantation-related infertility and optimizing assisted reproductive technologies.